Do Biliary Complications after Proton Beam Therapy for Perihilar Hepatocellular Carcinoma Matter? - Yoo, Gyu Sang (Cancers (Basel), 2020)
We aimed to evaluate the biliary complications and efficacy of proton beam therapy (PBT) for hepatocellular carcinoma (HCC). We retrospectively analyzed 167 patients who received PBT with ≥ 75 GyRBE of biological effective dose with /β = 10 for primary HCC. The perihilar region was defined as a 1-cm area extending from the right, left, and common hepatic ducts, including the gallbladder and cystic duct. PBT-related biliary complications were defined as follows: significant elevation in bilirubin level to > 3.0 mg/dL; elevation to more than twice of the baseline level after the completion of PBT; or newly developed radiological biliary abnormalities, which were not caused by HCC progression, comorbidities, or other treatments. Eighty (47.9%) had perihilar HCC. PBT-related events occurred in seven (4.2%), three of whom had perihilar HCC. Radiologic biliary abnormalities developed in 12 patients (7.2%); however, no events were PBT-related. All patients who experienced PBT-related biliary complications had underlying liver cirrhosis. The albumin-bilirubin grade was identified as an independent factor associated with PBT-related biliary complications. PBT at the current dose showed a low rate of PBT-related biliary complications even for patients with perihilar HCC. PBT for HCC patients with risk factors requires attention to reduce PBT-related biliary complications.